Maya and the robot - Ewing, Eve L. (Kokila, 2022)
Science-loving fifth grader Maya Robinson is feeling lonely at the start of school without her two best friends MJ and Jada who are in a different class. Discovering a half-finished robot in the back room of Mr. Mac's neighborhood store, Maya channels her loneliness into getting the robot, Ralph, up and running and find a newfound friend and source of pride.